Technologies 4.0 and their impact on international trade - Żukrowska, Katarzyna (Technologie 4.0 i ich wpływ na międzynarodową wymianę handlową, 2019)
Revolution 4.0 has a multidimensional impact on international trade, international division of labor, prospects of catching-up and overcoming the development gap in all the groups of countries which lag behind. The role that the resolution in question can play here derives from acceleration and simplification of international communication which is linked with essential fall of international communications costs, as well as increased access to communications technologies. All this is followed by changes in the structure of the world economy and methods of conducting business, as all reflected in changes of foreign trade measured by geographic flows, volumes, structure. Technologies 4.0, mainly, the ICT, lower the costs of foreign exchange and accelerate the procedures, which are applied in case of transborder transfers of foods and services. Structure of the economy, changes in international trade and its geographic flows impose consecutive changes in applied policies (industrial and trade), which are conducted by states. Without their change – access and full application of technologies 4.0 will be limited. Limitations in this specific area will have negative impact on rates of growth, structure changes, innovativeness, productivity, etc. In other words use of full existing potential of the technologies in particular economy will be limited, postponing its development. The revolution is not limited to ICT but it also covers use of Artificial Intelligence (AI) in such activities as: production, organization and processing
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 52-66
Keywords: revolution 4.0; ICT; international trade; development; protection; opening of market; rewolucja 4.0; handel międzynarodowy; rozwój; protekcja; otwarcie rynku